Remembering Jay S. Birnbrauer. Issue 4 (21st February 2018) - Jones, B. Max; Ralph, Alan; Mazzucchelli, Trevor G.
Abstract : Professor Jay Spencer Birnbrauer peacefully passed away on November 1, 2017, aged 83, in Perth, Western Australia. Known to his friends and colleagues in Australia as 'Birny', he was a pioneer of applied behaviour analysis on both the Australian and world stage. He contributed to the development of behaviour-analytic technology for children with intellectual and developmental disabilities in the 1960s and played a central part in the formation of the Australian Behaviour Modification Association (known today as the Australian Association for Cognitive and Behaviour Therapy) in the 1970s. He was a purist in the field of applied behaviour analysis (ABA) and was relentless in his efforts to see ABA being provided to children with a developmental disability and their families. Birny's influence in Australia, and particularly Western Australia, was mainly imparted through his role with the Master of Applied Psychology program at Murdoch University. His most widely known piece of work, the Murdoch Early Intervention Program, was an early and important replication of Lovaas's evaluation of early intensive behavioural intervention for children with autism. Birny contributed significantly to our field and to many people's lives. He is remembered often and fondly by his many friends and colleagues.